Character Education, Local Wisdom, and the Profile of Pancasila Students: Challenges and Potential Approach - Masrukhi; Wijayanti, Tutik; Melynda; Saputri, Aprilia Rizki (Indonesian Research Journal in Education |IRJE|, 2024)
The present study examines challenges and approaches involved in improving character education, namely through the Pancasila Student Profile (P5), at junior high schools located in Semarang City. The data was gathered by employing a qualitative methodology, which involved classroom observations, focus group discussions, and interview. The findings reveal that Junior high schools encounter character challenges such as bullying, minor crimes, disrespect, and internet use are examples. Student discipline, responsibility, social contact, and social media/peer pressure are issues. Academic expectations increase stress. Character education is integrated into the curriculum, teacher training, and extracurricular activities to address these challenges by introducing local wisdom in traditional arts, folk games, and teamwork. Local wisdom-based understanding, role-playing, and social action initiatives are taught. Local wisdom-based character education shapes students' behaviour and attitudes, preparing them for future problems and conserving national traditions. Schools may foster well-rounded students by fostering positive character, student participation, and cultural diversity.